Book Review: The Country and the City - Jerry D. Johnson; Craig B. Howley (Journal of Research in Rural Education, 2000)
The intent of this essay review is to introduce, via his major work, the ideas of Raymond Williams and to suggest a translation of his significant arguments into the rural North American experience of schooling. This major work is The Country and the City (Williams, 1973).